The Effect Of N-Hexane, Ethyl Acetate, And Water Fractions Of Peanut Seeds (Arachis Hypogaea L.) On Antioxidant Activity With The Dpph Method - Retno, Kumoro; Liandhajani, Liandhajani; Putra, Andriansyah Mas Jaya (Al Makki Health Informatics Journal, 2025)
Free radicals are one of the causes of various degenerative diseases, for example cardiovascular, high blood pressure, stroke, cirrhosis of the liver, cataracts, diabetes mellitus, and cancer. Antioxidants are compounds that can absorb or neutralize free radicals so that they are able to prevent disease due to damage to body cells, one of the plants that can be used as a natural source of antioxidants is peanut seeds. Peanut seeds contain flavonoid compounds that have the ability to act as antioxidants. The purpose of this study is to determine the presence of antioxidant activity, maximum concentration, EC50(ppm), and differences in antioxidant activity of n-hexane fraction, ethyl acetate fraction, and water fraction in peanut seeds in vitro. The method used in peanut seed extraction is remaceration with 96% ethanol solvent for 3 days. This study used solvents of n-hexane fraction, ethyl acetate fraction, and water fraction. Fractionation process for separation of compounds. The results of each fraction were tested by phytochemical screening and tested by thin layer chromatography (KLT). Quantitative analysis of antioxidants using the DPPH method at a maximum wavelength of 517.5 nm. The results of the study showed that the average yield from the extract was 24.15%. The n-hexane fraction, ethyl acetate fraction, and water fraction of peanut seed extract were 20.33%, 25.61%, 33.28%, respectively. The results of phytochemical screening obtained the results that were positive for flavonoids containing antioxidants in vitro. An average of EC50(ppm) was obtained in the standard quercetin, n-hexane fraction, ethyl acetate fraction, water fraction of 12.02 ppm; 10.62 ppm; 12.25 ppm; 11.75 ppm. The results of the statistical test according to ANAVA I showed that the significance was more than 0.05 which was 0.105 so that it can be concluded that the difference was not significant between the concentration groups of n-hexane, ethyl acetate, and water fractions of peanut seed extract in invitro antioxidant activity.